Developing English-Speaking Worksheets for the Culinary Arts Study Program at Vocational School - Furwana, Dewi; Syam, Andi Tenrisanna; Wisran; Maskur (Inspiring: English Education Journal, 2024)
This study aimed to create suitable English-speaking worksheets for culinary art students at Vocational School and to assess the perceptions of both students and teachers regarding the worksheets. The research followed a Research and Development (R&D) methodology using the 4-D Design Model, which includes the stages of defining, designing, developing, and disseminating. The participants were 24 tenth-grade culinary art students from SMK Negeri 1 Palopo. Data were gathered through a needs analysis questionnaire, expert validation sheets, and feedback on the worksheets from students and teachers. The study produced four culinary-related topics for the speaking worksheets, covering basic culinary skills, service, operations, and table manner. The findings revealed an average score of 375 (93.75%) from students and 3.72 (93%) from teachers, both classified as “Excellent”, indicating the worksheets were well-suited for the culinary arts program and could serve as a resource to enhance students’ motivation in learning English.